Prognostic factors of traumatic optic neuropathy based on multimodal analysis—Especially the influence of postoperative dressing change and optic nerve blood supply on prognosis - Liu, Xueru; Wang, Jing; Zhang, Wenyue; Li, Lunhao; Zhang, Leilei; Xiao, Caiwen (Frontiers in Neurology, 2023)
Objective: To investigate the critical prognostic factors of patients with traumatic optic neuropathy (TON) treated with endoscopic transnasal optic canal decompression (ETOCD) and to perform multimodal analysis based on imaging examinations of optical coherence tomography angiography (OCTA) and CT scan. Subsequently, a new prediction model was established. Methods: The clinical data of 76 patients with TON who underwent decompression surgery with the endoscope-navigation system in the Department of Ophthalmology, Shanghai Ninth People’s Hospital from January 2018 to December 2021 were retrospectively analyzed. The clinical data included demographic characteristics, reasons for injury, interval between injury and surgery, multimode imaging information of CT scan and OCTA, including orbital fracture, optical canal fractures, vessel density of optic disc and macula, and the times of postoperative dressing change. Binary logistic regression was used to establish a model for best corrected visual acuity （BCVA）after treatment as a predictor of TON outcome. Results: Postoperative BCVA improved in 60.5% (46/76) patients and did not improve in 39.5% (30/76) patients. The times of postoperative dressing change had a significant impact on the prognosis. Other factors affecting the prognosis were microvessel density of the central optic disc, the cause of injury, and the microvessel density above the macula. The area under the raw current curves of the predictive model was 0.7596. Conclusions: The times of dressing changes after the operation, i.e., continuous treatment, is the key factor affecting prognosis. The microvessel density in the center of the optic disc and superior macula, quantitatively analyzed by OCTA, is the prognostic factor of TON and may be used as a prognostic marker of TON.